2013
DOI: 10.1074/jbc.m113.469916
|View full text |Cite
|
Sign up to set email alerts
|

Zn2+ Mediates High Affinity Binding of Heparin to the αC Domain of Fibrinogen

Abstract: Background:The interaction of heparin with fibrinogen compromises its anticoagulant activity. Results: Zn 2ϩ promotes heparin binding to His-544 -His-545 on the fibrinogen ␣-chain. Conclusion: We identified a novel Zn 2ϩ -dependent heparin binding site on fibrinogen. Significance: Platelet release of Zn 2ϩ at sites of vascular injury may promote heparin binding to fibrinogen, thereby further attenuating the anticoagulant activity of heparin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 50 publications
1
41
0
Order By: Relevance
“…Another Zn 2+ -binding region has been identified in the αC-domain and also involves histidine residues (His-α544 and His-α545). 75 Binding of Zn 2+ to this region is thought to induce a change in the conformation of the protein. 75 Based on several studies, Zn 2+ binding to fibrinogen has an average K d of ∼1–18 μM, but the individual contributions of the two groups of sites are unknown.…”
Section: Impact Of Zn 2+ On Protein–gag Interactiomentioning
confidence: 99%
See 2 more Smart Citations
“…Another Zn 2+ -binding region has been identified in the αC-domain and also involves histidine residues (His-α544 and His-α545). 75 Binding of Zn 2+ to this region is thought to induce a change in the conformation of the protein. 75 Based on several studies, Zn 2+ binding to fibrinogen has an average K d of ∼1–18 μM, but the individual contributions of the two groups of sites are unknown.…”
Section: Impact Of Zn 2+ On Protein–gag Interactiomentioning
confidence: 99%
“… 75 Binding of Zn 2+ to this region is thought to induce a change in the conformation of the protein. 75 Based on several studies, Zn 2+ binding to fibrinogen has an average K d of ∼1–18 μM, but the individual contributions of the two groups of sites are unknown. 27 , 36 , 75 …”
Section: Impact Of Zn 2+ On Protein–gag Interactiomentioning
confidence: 99%
See 1 more Smart Citation
“…Underlying coagulopathy or thrombocytopenia should be corrected by transfusion of plasma, cryoprecipitate, or platelets as clinically indicated. After surgery, during the acute phase response, optimal heparin management is challenging since heparin binds some acute phase reactants, such as vitronectin, 14 fibrinogen, 15 plasminogen activator inhibitor 1 16 and von Willebrand factor (VWF). 17 Heparin therapy should frequently be monitored, and the dose should be adjusted at the target anti-Xa of 0.2 to 0.4 units/mL as soon as clinically tolerated.…”
Section: Hemostasis Management Acute Phasementioning
confidence: 99%
“…Interestingly, a recent study by Fredenburgh et al has revealed that fibrinogen, like HRG, also binds heparin with high affinity in a Zn 2+ -dependent manner [74]. Fibrinogen is a glycoprotein present in plasma at a concentration of around 6-12 μM [71,75].…”
Section: Ffa-mediated Alterations In Plasma Zinc Speciation: Implicatmentioning
confidence: 99%